1993
DOI: 10.1182/blood.v82.5.1422.bloodjournal8251422
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients with invasive fungal disease who received adjunctive therapy with recombinant human macrophage colony- stimulating factor

Abstract: Mortality of bone marrow transplant (BMT) patients who develop invasive fungal infection is greater than 80%. Long-term follow-up of 46 consecutive BMT patients who received recombinant human macrophage colony-stimulating factor (rhM-CSF) as adjunctive therapy with standard antifungal treatment who were entered into phase I/II trials at The Fred Hutchinson Cancer Research Center is reported. rhM-CSF (100 micrograms/m2 to 2,000 micrograms/m2; Chiron/Cetus Corporation, Emeryville, CA) was administered from day 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In a small non-comparative study, administration of GM-CSF was associated with a complete or partial response in six of eight neutropenic patients with documented IFI (Bodey et al, 1994). The survival of bone marrow transplant patients with invasive candidiasis and a Karnofsky score >20% who received recombinant human M-CSF as adjunctive therapy, was significantly higher compared to historical controls (Nemunaitis et al, 1993). In a non-comparative pilot study of 11 acquired immunodeficiency syndrome (AIDS) patients with fluconazole-refractory oropharyngeal candidiasis, adjunctive treatment with GM-CSF (sargramostim) appeared to exert a beneficial effect (Vazquez et al, 2000).…”
Section: Clinical Evidence Of Cytokine Use In the Treatment Or Prevenmentioning
confidence: 91%
“…In a small non-comparative study, administration of GM-CSF was associated with a complete or partial response in six of eight neutropenic patients with documented IFI (Bodey et al, 1994). The survival of bone marrow transplant patients with invasive candidiasis and a Karnofsky score >20% who received recombinant human M-CSF as adjunctive therapy, was significantly higher compared to historical controls (Nemunaitis et al, 1993). In a non-comparative pilot study of 11 acquired immunodeficiency syndrome (AIDS) patients with fluconazole-refractory oropharyngeal candidiasis, adjunctive treatment with GM-CSF (sargramostim) appeared to exert a beneficial effect (Vazquez et al, 2000).…”
Section: Clinical Evidence Of Cytokine Use In the Treatment Or Prevenmentioning
confidence: 91%
“…In clinical trials, Nemunaitis et al [22,23] demonstrated that the combined use of M-CSF with standard anti-fungal treatment in patients with invasive fungal infections after bone marrow transplantation resulted in an improvement of the survival rate compared with the control. Ohno et al [24] reported that the administration of M-CSF signi®cantly reduced the incidence and duration of febrile neutropenia during the intensive consolidation therapy, and shortened the period required to complete three courses of consolidation chemotherapy in acute myelogenous leukaemia.…”
mentioning
confidence: 99%
“…34) In addition, a protective effect of M-CSF against fungal infection via monocytes was reported in vitro and in vivo. [35][36][37][38][39] In summary, the present findings suggest that granulocyte function should be improved to prevent infection after chemotherapy. Administration of M-CSF is effective for preventing the dysfunction of neutrophils, resulting in the prevention of febrile neutropenia following chemotherapy.…”
Section: Discussionmentioning
confidence: 88%